Electrospinning of PVP Nanofibers and Optimization with Taguchi Experimental Design - Pinarbasi, Aysun; Çallıoğlu, Funda Cengiz (My University, 2022)
The aim of this study is the determination of optimum process parameters which will provide the finest and the most uniform electrospun Polyvinylpyrrolidone (PVP) based nanofibers with Taguchi experimental design. For the designed experimental setup, parameters (solvent type, polymer concentration, voltage, distance between the electrodes, solution feed rate and humidity) were used which effect the electospinning process significantly. For this purpose, the appropriate orthogonal array was selected to determine the factors and levels at Taguchi experimental design application. The experimental design aimed which provides to be reduced the number of experiments and minimised the effect of uncontrollable factors with less experiments to obtain target value by using Taguchi orthogonal arrays. In the experimental studies of paper, firstly PVP polymer solutions such as conductivity, surface tension and viscosity were determined with various PVP concentrations (10, 12, 14 wt %) and solvents (ethanol, dimethylformamide, dimethylacetamide, chloroform, acetic acid and distilled water). Scanning Electron Microscope (SEM) images of electrospun PVP based nanofibrous surfaces were obtained, average fiber diameter and fiber diameter coefficient values were calculated by ImageJ image analyses software and fiber diameter distribution histogram curves were obtained by SPSS program. Experimental results were analyzed and commented by Taguchi method in MINITAB program with variance analysis. According to the results; solvent type has the highest effect on the electrospinning of PVP nanofibers. In this study, it is predicted to save in terms of time and cost with decreasing the number of experiments by Taguchi experiment design.
Keywords: Optimization; electrospinning; Polyvinylpyrrolidone; Taguchi experimental design; nanofiber.; Polyvinylpyrrolidone; electrospinning; optimization; Taguchi experimental design; nanofiber.